2000
DOI: 10.1097/00004647-200011000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Similarity and Robustness of PET and SPECT Binding Parameters for Benzodiazepine Receptors

Abstract: The single photon emission computed tomography (SPECT) radiotracer [123I]iomazenil is used to assess benzodiazepine receptor binding parameters. These measurements are relative indices of benzodiazepine receptor concentration (B'max). To evaluate the ability of such indices in accurately accessing the B'max the authors compared them with absolute values of B'max, measured using positron emission tomography (PET). The authors performed SPECT, PET, and magnetic resonance imaging (MRI) studies on a group composed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…Thirteen rhesus monkeys were imaged with [ 11 C]flumazenil and positronemission tomography (PET) to image GABA A receptor availability at baseline-that is, when drug naïve-and then up to three times during alcohol withdrawal. [ 11 C]flumazenil and [ 123 I]iomazenil both measure cortical GABA A receptors, and the outcome measures are highly correlated (19,20). One group of animals (n = 7) consumed only alcohol for up to 20 wk (alcoholonly group) before alcohol withdrawal, and a separate group of animals (n = 6) consumed alcohol and nicotine for up to 20 wk and then continued to consume nicotine over the course of alcohol withdrawal (alcohol + nicotine group).…”
Section: Gaba a Receptor Availability Is Related To Alcohol And Tobacmentioning
confidence: 99%
“…Thirteen rhesus monkeys were imaged with [ 11 C]flumazenil and positronemission tomography (PET) to image GABA A receptor availability at baseline-that is, when drug naïve-and then up to three times during alcohol withdrawal. [ 11 C]flumazenil and [ 123 I]iomazenil both measure cortical GABA A receptors, and the outcome measures are highly correlated (19,20). One group of animals (n = 7) consumed only alcohol for up to 20 wk (alcoholonly group) before alcohol withdrawal, and a separate group of animals (n = 6) consumed alcohol and nicotine for up to 20 wk and then continued to consume nicotine over the course of alcohol withdrawal (alcohol + nicotine group).…”
Section: Gaba a Receptor Availability Is Related To Alcohol And Tobacmentioning
confidence: 99%
“…Obviously, performing scans of minimal duration, employing a model that requires no blood sampling and yet obtaining accurate parameters is a critical factor for the success of clinical and preclinical experiments. All these questions have been thoroughly assessed in human and other primate studies regarding kinetic, graphical and equilibrium analyses [7,20,22,23,33,[40][41][42]. Nevertheless, no study on rodent GABA A quantification with SPECT exists.…”
Section: Discussionmentioning
confidence: 99%
“…the reference region, corresponds to the binding potential of the tracer [24]. Previously, Millet et al [22] established the reliability of binding parameter estimations analyzing delayed activity acquired between SPECT scans for [ 123 I]IMZ binding quantification in humans. In this study, we performed this type of analysis for consequent frames of 10 or 20 min starting from the 40th minute of acquisition and we concluded that activity from an image 50-70 min postinjection provides the parameters that best correlate with parameters obtained with SRTM2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations